1987
DOI: 10.1164/ajrccm/136.5.1140
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic-Mediated Bronchoconstriction Induced by Prostaglandin D2, Its Initial Metabolite 9α, 11β-PGF2, and PGFin Asthma

Abstract: In this study, we have investigated the contribution of cholinergic-mediated bronchoconstriction in the airway response provoked by inhaled prostaglandin (PG)D2, its metabolite 9 alpha, 11 beta-PGF2, and PGF2 alpha, which are generated during mast cell activation in vivo and are potent bronchoconstrictor agonists in humans. The effect of prior inhalation of 1 mg ipratropium bromide (IB) on the bronchoconstrictor response to inhaled methacholine (MCh), PGD2, 9 alpha, 11 beta-PGF2, and PGF2 alpha was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…We also found that PGFS mRNA was expressed in PBL as well as lung. As PGD 2 is increased in alveolar lymphocytes as well as in macrophages, eosinophils and mast cells after a challenge with an inflammatory antigen [23–25], we examined the effect of Con A, which is considered to be a T lymphocyte‐specific mitogen [26], on expression of PGFS mRNA in PBL. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also found that PGFS mRNA was expressed in PBL as well as lung. As PGD 2 is increased in alveolar lymphocytes as well as in macrophages, eosinophils and mast cells after a challenge with an inflammatory antigen [23–25], we examined the effect of Con A, which is considered to be a T lymphocyte‐specific mitogen [26], on expression of PGFS mRNA in PBL. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mast cell-derived mediators induce the classical features of the early asthmatic reaction in vivo , inducing bronchoconstriction, mucus secretion and mucosal oedema (for reviews see (Bradding and Cruse, 2008; Bradding et al, 2006; Brightling et al, 2003a; Moiseeva and Bradding, 2011)). For example, several studies have identified an increase in histamine, prostaglandin D 2 (PGD 2 ) and leukotriene C 4 (LTC 4 ) in the BAL fluid of asthma subjects following bronchial allergen challenge (Casale et al, 1987; Liu et al, 1991; Murray et al, 1986; Sedgwick et al, 1991; Wenzel et al, 1988; Wenzel et al, 1990; Wenzel et al, 1991) and that the early asthmatic reaction is significantly alleviated with the administration of potent selective inhibitors of histamine, LTC 4 and to a lesser extent PGD 2 (Beasley et al, 1987; Curzen et al, 1987; Findlay et al, 1992; Rafferty et al, 1987; Taylor et al, 1991). These mediators are most likely derived from mast cells in the bronchial mucosa because histamine, PGD 2 and LTC 4 are all released from human lung mast cells in vitro with remarkably similar kinetics to the allergen challenge studies (Schleimer et al, 1986).…”
Section: Mast Cells In Asthmamentioning
confidence: 99%
“…Thus, at least some of the bronchoconstrictor activity of en dogenously generated PGD2 may result from the ac tion of one of its immediate metabolites. Using the potent and selective muscarinic cholinergic antagon ist, ipratropium bromide, administered by inhalation in a dose of 1 mg, we have shown that a significant proportion of bronchoconstriction mediated both by PGD2 and 9 a,1I/LPGF2 but not PGF2a occurs from stimulation of vagal reflexes in the airways [44].…”
Section: Pharmacological Dissection O F the Immediate Asthmatic Reactionmentioning
confidence: 99%